The influence of internal audit and internal control toward fraud prevention - Bregitta Roemkenya Madolidi Handoyo; Bunga Indah Bayunitri (International Journal of Financial, Accounting, and Management, 2021)
Purpose: This study aimed to determine whether there is an influence of internal audit and internal control on fraud prevention at PT Pos Indonesia (Persero) Bandung. Research methodology: This study used the verification method, the sampling technique used in this study was a combination of non-probability with a saturated sampling technique. The sample in this study were employees at PT Pos Indonesia (Persero) Bandung City, amounting to 91 people. The Program used in analyzing data was Statistical Package for Social Sciences (SPSS) Ver25.00. Results: The results showed that internal audit and internal control influence the prevention of fraud in PT Pos Indonesia (Persero) Bandung. In addition, the magnitude of the influence of internal audit and control in contributing to the prevention of fraud by 68.8%. Limitations: The study was only conducted at PT Pos Indonesia (Persero), Bandung City. Contribution: This research is expected to be able to provide input for PT Pos Indonesia (Persero) Bandung City which is aimed at improving improvements in minimizing and preventing fraud, and can be used as additional information for related parties.